Wutou decoction attenuates the synovial inflammation of collagen-induced arthritis rats via regulating macrophage M1/M2 type polarization. (30th January 2023) - Lin, Weiji; Shen, Pan; Huang, Ying; Han, Liang; Ba, Xin; Huang, Yao; Yan, Jiahui; Li, Tingting; Xu, Lijun; Qin, Kai; Chen, Zhe; Tu, Shenghao
Abstract: Ethnopharmacological relevance: Thousands of years of clinical practice in the treatment of joint-related diseases support the efficacy and safety of Wutou decoction (WTD). Nevertheless, the lack of pharmacological evidence and unclear mechanisms make it difficult for WTD to become a recognized complementary therapy for the treatment of rheumatoid arthritis (RA). Aim of the study: This study aimed to investigate the effect of WTD against synovial inflammation in RA and whether this effect depends on the regulation of macrophage polarization. Materials and methods: Sprague-Dawley rats were used to establish the collagen-induced arthritis (CIA) model. WTD with low and high doses was administered for 45 days. RAW264.7 cells were stimulated by lipopolysaccharide (LPS) or interleukin (IL)-4 to polarize M1 and M2 macrophages, which were pre-treated with WTD extract for 4 h. The anti-arthritic and anti-inflammatory effects of WTD were studied using arthritis score, histopathological staining, immunostaining, and enzyme-linked immunosorbent assay (ELISA). The polarization state of RAW264.7 cells and related pro/anti-inflammatory cytokines was detected by ELISA, reverse transcription quantitative polymerase chain reaction and western blotting. Western blotting and immunofluorescence were used to investigate the effect of WTD on nuclear factor kappa-light-chain-enhancer of activated B cells (NF-κB) and peroxisome proliferator-activated receptors γ (PPARγ) activation both in vivo and in vitro . Results: WTD significantly reduced the arthritis score and the pathological damage of the knee joint and decreased the expression of tumor necrosis factor alpha (TNF-α), IL-6 in serum, TNF-α, IL-1β, monocyte chemoattractant protein-1 (MCP-1), and matrix metalloproteinase-3 (MMP3) in the knee synovium. WTD inhibited M1 type polarization and promoted M2 type polarization, both in vitro and in vivo, and reduced the expression of pro-inflammatory cytokines while increasing the expression of anti-inflammatory cytokines. Experiments showed that WTD inhibited the phosphorylation of NF-κB and downstream p38 in the synovium of CIA rats and LPS-induced M1 type polarized RAW264.7 cells. In addition, PPARγ expression in the synovium of CIA rats was mainly located in the cytoplasm, and WTD treatment increased the nuclear translocation of PPARγ, which was further verified in RAW264.7 cells. Conclusions: NF-κB and PPARγ regulating M1 and M2 macrophage polarization and subsequent secretion of pro-inflammatory and anti-inflammatory cytokines are the underlying mechanisms of WTD that ameliorate RA synovial inflammation. Graphical abstract: Image 1 Highlights: Wutou decoction alleviates joint destruction and inhibit synovial inflammation in experimental arthritis. Wutou decoction inhibit macrophage M1 type polarization through inhibiting phosphorylation of NF-κB and p38. Wutou decoction promote macrophage M2 type polarization by increasing nuclear translocation of PPARγ and Stat6. Wutou decoction made its anti-arthritic effects by a combination of Quxie and Fuzheng.